Comparative study of oncology patients' quality of life - Meneguin, Silmara [UNESP]; Pollo, Camila Fernandes [UNESP]; Camargo, Heloiza Thaís Felipe [UNESP]; Honório, Heitor Marques; De Oliveira, César (Mark Allen Group, 2024)
Background: A cancer diagnosis has a significant impact on a person's life, both physically and emotionally. However, the oncology patients' QoL (QoL) at different stages of the disease has been under investigated. Aim: To assess and compare the QoL in three groups of oncology patients. Methods: A comparative study was carried out in an outpatient care service at a public hospital in the state of Sao Paulo. Data collection involved the use of the Palliative Performance Scale and the McGill QoL Questionnaire. Results: Most participants were women, Catholic and living with a partner. The Palliative Performance Scale revealed a predominance of stable patients (score: >70 points). Overall, palliative care patients had lower QoL scores compared to the other groups (p < 0.01). Conclusion: QoL was worse among palliative care patients. Advanced age, being in palliative care, and have a low-income were negatively associated with a patient's QoL.
Keywords: antineoplastic agents; humanisation; nursing of care; palliative care; QoL